THE INFLUENCE OF FASHION PRODUCT MARKETING STRATEGIES ON CONSUMER BUYING INTEREST IN GURLS CLUB IN BANDUNG CITY - Oktapriani, Melinda; Nurhayati (Journal of Economic Empowerment Strategy (JEES), 2024)
Club is a business operating in the fashion sector. According to the researcher, researchers found that there was a problem with consumer buying interest. This problem was thought to be because the design and hion product marketing strategies on consumer purchasing interest at the Gurls Club in Bandung City. The method applied in this research is a quantitative approach. Primary data was collected through non-participant observation, structured interviews and distributing questionnaires given to Gurlscolor of the product did not match consumer trends or tastes and the product quality and price were always compared with competitors. The aim of this research is to understand the impact of fas Club Bandung City consumers with a total of 98 respondents using the Slovin formula, while secondary data was through literature and internet studies. To analyze the data, reliability and validity tests, simple linear regression analysis, level of certainty of the coefficient of determination, Spearman level relationships, and hypothesis testing were used. Data collected from research shows that there is a positive correlation between Marketing Strategy and Consumer Buying Interest at the Gurls Club in Bandung City, and also shows that marketing strategy has a contribution or influence. Marketing strategy on consumer buying interest at the Gurls Club in Bandung City is around 75% influenced by marketing strategy, while the remaining 25% is influenced by other factors such as service quality. The obstacles faced by the Gurls Club are in its implementation, namely the designs and colors available are only intended for teenagers and adults and the lack of promotion carried out by the Gurls Club. Suggestions that researchers can convey are adding neutral and pastel product colors so that market segmentation can be used for all groups and adding promotional media.